2020
DOI: 10.1186/s40854-020-00203-3
|View full text |Cite|
|
Sign up to set email alerts
|

Applying multivariate-fractionally integrated volatility analysis on emerging market bond portfolios

Abstract: This study examines emerging market (EM) local bonds from a portfolio risk perspective and suggests methodologies for risk evaluation, on which the literature is limited. Despite the growth of EM bond funds in recent years, comprehensive studies regarding this industry have been scarce. In light of this, 203 different local bonds of EM countries—Indonesia, Brazil, India, South Africa, Mexico, and Turkey—are elaborated in terms of return, volatility, and cross-correlation features. This study focuses on an unto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…They found that the degree of integration of the series (their persistence) is inversely related to the maturity of the bonds. Finally, Demirel and Unal (2020) analysed 203 local bonds in the emerging markets of Indonesia, Brazil, India, South Africa, Mexico, and Turkey from a portfolio risk perspective; specifically, they estimated fractional models for risk evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the degree of integration of the series (their persistence) is inversely related to the maturity of the bonds. Finally, Demirel and Unal (2020) analysed 203 local bonds in the emerging markets of Indonesia, Brazil, India, South Africa, Mexico, and Turkey from a portfolio risk perspective; specifically, they estimated fractional models for risk evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Changes in market regimes have been identified extensively in the emerging markets by various authors (Demirel and Unal, 2020). The switches or changes in regimes observed in the markets are a function of a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…used variants on the Nelson-Siegel exponential components framework to model the yield curve; they showed that the three time-varying parameters may be interpreted as factors corresponding to the level, slope, and curvature respectively, and estimated autoregressive models for the factors to generate short-and long-term forecasts Demirel and Unal (2020). analysed 203 local bonds in the emerging markets of Indonesia, Brazil, India, South Africa, Mexico, and Turkey from a portfolio risk perspective; specifically, they estimated fractional models for risk evaluation.…”
mentioning
confidence: 99%